2022
DOI: 10.1136/bjophthalmol-2022-321357
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of endophthalmitis after vitrectomy relative to face mask wearing during COVID-19 pandemic

Abstract: Background/aimsTo determine the incidence and causative pathogens of endophthalmitis after vitrectomy during strict face mask wearing in the COVID-19 period.MethodsThis was a retrospective multicentre study including 31 ophthalmological institutions of the Japanese Retina and Vitreous Society or Japan-Clinical Retina Study group. Patients who had undergone vitrectomy during 2019, the pre-COVID-19 period, and from July 2020 to June 2021, the COVID-mask period, were studied. The results of cataract surgery were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…One study used the schlieren imaging technique to record airflow around the eyes while participants were wearing masks 12 . A multicenter study in Japan reported an increase in the incidence of endophthalmitis after vitrectomy following the start of the COVID-19 pandemic 15 . The same study also reported that the incidence of endophthalmitis after cataract surgery did not increase.…”
Section: Relationship Between Surgical Field Contamination By Patient...mentioning
confidence: 99%
“…One study used the schlieren imaging technique to record airflow around the eyes while participants were wearing masks 12 . A multicenter study in Japan reported an increase in the incidence of endophthalmitis after vitrectomy following the start of the COVID-19 pandemic 15 . The same study also reported that the incidence of endophthalmitis after cataract surgery did not increase.…”
Section: Relationship Between Surgical Field Contamination By Patient...mentioning
confidence: 99%
“…Several authors have associated the use of face masks skin eruptions, some involving S. aureus [77] including new occurrence or exacerbation of acne, rosacea, and seborrhoeic dermatitis [78]. Other authors note enrichment of the normal eye microbiota with S. aureus from exhaled breath and droplets while wearing a mask contributing to the development of eyelid inflammation (chalazion) [79,80] and infections of the cornea [81], also deeper eye infections in the context of treatments (endophthalmitis following vitrectomy) [82]. There is also some evidence that S. aureus can increase replication of the SARS-CoV-2 virus by 10-to 15-fold [83], though this seems more pertinent in the upper nose than on a mask, where the virus is unlikely to be replicating.…”
Section: Bacteria Detected: Potential Clinical Implicationsmentioning
confidence: 99%
“…18,19 On the contrary, regarding PPV, Sakamoto et al observed a higher rate of endophthalmitis relative to face mask wearing during the pandemic. 20 Some of their cases were associated with oral commensals, an unusual cause of post vitrectomy endophthalmitis. 20 Endogenous cases, on the other hand, have been on the rise 14 , especially those caused by fungal pathogens.…”
Section: Endophthalmitis and Covid-19mentioning
confidence: 99%
“…20 Some of their cases were associated with oral commensals, an unusual cause of post vitrectomy endophthalmitis. 20 Endogenous cases, on the other hand, have been on the rise 14 , especially those caused by fungal pathogens. Schroff et al, 21 reported on 5 eyes with endophthalmitis in 7 patients with severe COVID-19 pneumonia and long-term CS therapy (80-180 days).…”
Section: Endophthalmitis and Covid-19mentioning
confidence: 99%